2021
DOI: 10.3390/jcm10061319
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Increased Risk of Early Severe Neonatal Morbidity in Late Preterm and Early Term Infants

Abstract: Although the risk of neonatal mortality is generally low for late preterm and early term infants, they are still significantly predisposed to severe neonatal morbidity (SNM) despite being born at relatively advanced gestations. In this study, we investigated maternal and intrapartum risk factors for early SNM in late preterm and early term infants. This was a retrospective cohort study of non-anomalous, singleton infants (34+0–38+6 gestational weeks) born at the Mater Mother’s Hospital in Brisbane, Australia f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 45 publications
(58 reference statements)
1
10
0
8
Order By: Relevance
“…Several studies have demonstrated that maternal factors (such as sociodemographic factors, obesity, smoking, and hypertension) and neonatal factors (lower birth weight and earlier gestational age) are associated with neonatal morbidity and mortality. [13][14][15][16][17] Recognizing that maternal factors directly impact neonatal outcomes and that maternal risk systems are being adopted in clinical practice, we sought to determine if a single-risk stratification system could be used for both maternal and neonatal outcomes. Our findings supported our initial hypothesis and are consistent with prior studies that earlier gestational age and lower birth weight are associated with a higher risk of adverse neonatal outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that maternal factors (such as sociodemographic factors, obesity, smoking, and hypertension) and neonatal factors (lower birth weight and earlier gestational age) are associated with neonatal morbidity and mortality. [13][14][15][16][17] Recognizing that maternal factors directly impact neonatal outcomes and that maternal risk systems are being adopted in clinical practice, we sought to determine if a single-risk stratification system could be used for both maternal and neonatal outcomes. Our findings supported our initial hypothesis and are consistent with prior studies that earlier gestational age and lower birth weight are associated with a higher risk of adverse neonatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings supported our initial hypothesis and are consistent with prior studies that earlier gestational age and lower birth weight are associated with a higher risk of adverse neonatal outcome. 14,15,17 Among neonates born at term gestation and those at low risk for complication, maternal risk scores constructed for maternal morbidity appear to provide little to no additional information on neonatal risk of low Apgar.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of most neonatal diseases in infants in the NICU in Xiangxi significantly increased with decreased gestational age, especially jaundice. In addition, the delivery method of pregnancy had significant impact on neonatal disease (30). The prevalence of CD was significantly higher than that of VD (31).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Several factors are impacted in adverse neonatal outcomes, although few studies have examined factors specifically associated with SNM. [5][6][7] Misra and colleagues (2003) proposed a multiple determinants framework for conceptualizing the complex relationships that influence perinatal (including neonatal) health, 8 and implicate interrelated distal social environmental factors (e.g., socioeconomic status, ethnicity), proximal biomedical (e.g., chronic diseases) and behavioural (e.g., smoking) responses, and intermediate diseases and pregnancy complications in the pathways to poor outcomes.…”
Section: Introductionmentioning
confidence: 99%